Pengembangan Instrumen Kecakapan Kerja Mahasiswa (Rasch Model Analisis) - Nurlatifah, Sari; Supriatna, Mamat; Yudha, Eka Sakti; Julius, Andre (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Employability Skills for College Students in University are an asset that can bring students closer to being ready to enter the world of work. Employability Skill can be interpreted as a series of characteristics including knowledge, attitudes, and skills that make a person capable of being trained. To get a general trend or a long work profile students need an instrument to reveal these variables. This study aims to develop employability skill instruments that are psychometrically tested both in terms of validity testing and instrument reliability testing using the RASCH model analysis method. The research instrument has been tested on 728 people. The results showed that from testing the instrument's validity using the RASCH model analysis on Outfit MNSQ, Outfit ZSTD, and Pt Measure Corr, of the 54 items developed, a total of 48 items met psychometric standards. The instrument's reliability on Cronbach's alpha value is in very good criteria, even in terms of reliability a person is in the very good category, and item reliability is in the special category. Therefore, the student employability skills instrument meets psychometric requirements and can be used as an instrument to measure student employability skills.